Comparative effects of whey and casein proteins on satiety in overweight and obese individuals: A randomized controlled trial - Pal, Sebely; Radavelli-Bagatini, Simone; Hagger, Martin; Ellis, Vanessa (Nature Publishing Group, 2014)
Background/Objective: Dairy protein seems to reduce appetite by increasing satiety and delaying the return of hunger and subsequently lowering energy intake compared with fat or carbohydrate. The aim of this study was to compare the effect of whey with that of casein proteins on satiety in overweight/obese individuals. Methods/Subjects: This was a randomized, parallel-design 12-week-long study. Seventy subjects with a body mass index between 25 and 40 kg/m2 and aged 18–65 years were randomized into one of three supplement groups: glucose control (n=25), casein (n=20) or whey (n=25) protein. Before commencing the study, at weeks 6 and 12 of the treatment, a Visual Analogue Scale (VAS) was used to measure subjective sensations of appetite before lunch and before dinner. Results: Rating for VAS (mm) at 6 and 12 weeks showed significantly higher satiety in the whey group compared with the casein (P=0.017 and P=0.025, respectively) or control (P=0.024 and P=0.032, respectively) groups when measured before lunch. Similarly, at 6 and 12 weeks, the score for fullness was also significantly higher in the whey group compared with both casein (P=0.038 and P=0.022, respectively) and control (P=0.020 and P=0.030, respectively) groups. However, these short-term effects on satiety from dairy whey proteins did not have any long-term effects on energy intake or body weight over 12 weeks compared with casein. Conclusions: Collectively, whey protein supplementation appears to have a positive and acute postprandial effect on satiety and fullness compared with casein and carbohydrate supplementation in overweight and obese individuals.